2020
DOI: 10.2147/opth.s288047
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison and Evaluation of Prelens Tear Film Stability by Different Noninvasive in vivo Methods</p>

Abstract: Purpose Prelens tear film stability of soft contact lens (SCL) play an important role for contact lens discomfort. In this study, we investigated the association between two types of noninvasive methods and evaluated the tear film stability with SCL using the methods. Patients and Methods In experiment 1, images of ring mire were recorded with a keratograph after focusing the pigment located at the front or back of the SCL. Interferometry and videokeratoscopy were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…TALB is known to occur immediately after eye-opening when there is no lipid layer on the SCL surface due to a thin aqueous layer tear, and rarely observed in bare eye. 24 In our study, we found a significant decrease in TALB among the SH-SCL delefilcon A lens wearers compared to the SCL narafilcon A lens wearers. The conventional SH SCLs (narafilcon A) has a low water content of 30% to 40% in all the layers such that the SCL surface is water-repellent, and tears evaporate immediately and easily from the surface.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…TALB is known to occur immediately after eye-opening when there is no lipid layer on the SCL surface due to a thin aqueous layer tear, and rarely observed in bare eye. 24 In our study, we found a significant decrease in TALB among the SH-SCL delefilcon A lens wearers compared to the SCL narafilcon A lens wearers. The conventional SH SCLs (narafilcon A) has a low water content of 30% to 40% in all the layers such that the SCL surface is water-repellent, and tears evaporate immediately and easily from the surface.…”
Section: Discussionsupporting
confidence: 48%
“… 21 Another study by Guillon et al 35 showed that the mean NIBUT of delefilcon A was longer (9.2 seconds) than that of narafilcon A (5.1 seconds, P = 0.006). The recent study by Itokawa et al 24 showed that the NIBUT measured by Keratograph 5M did not correlate to that measured by DR-1α in the eyes with SCL and proposed the possibilities that Keratograph 5M frequently captures the tear dynamics in the posterior but not the anterior surface of SCL, resulting in inaccurate NIBUT values. In our measurements, Keratograph 5M was unstable as reported by Itokawa et al; thus, we used DR-1α measurements for the NIBUT analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite scientific evidence supporting the evaluation of in vivo wettability by corneal topography during soft contact lens wear [18,19,22,23], this technique has limitations that should be explored in future studies. In this sense, a study by Itokawa et al [24] reported no correlation between the in vivo wettability measured by videokeratoscopy (objective) and interferometry (subjective) using two soft contact lenses. Additionally, they showed that the videokeratoscopy showed differences between both contact lenses, while not the interferometry.…”
Section: Discussionmentioning
confidence: 95%
“…This allows the measurement of noninvasive breakup time which is more unambiguous to interpret than the one measured with fluorescein (as the FBUT might be related with local thinning of the tear film rather than with actual breakup event) and has been shown as potentially having a stronger correlation with patient discomfort. Furthermore, noninvasive techniques can be readily used by a broader range of medical personnel, such as technicians and nurses, which allows for more rapid and broadly available diagnostics of DED [87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%